The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1038/leu.2010.99
|View full text |Cite
|
Sign up to set email alerts
|

Deletions of the transcription factor Ikaros in myeloproliferative neoplasms

Abstract: Transformation to acute leukemia is a major complication of myeloproliferative neoplasms (MPNs), however, the genetic changes leading to transformation remain largely unknown. We screened nine patients with post-MPN leukemia for chromosomal aberrations using microarray karyotyping. Deletions on the short arm of chromosome 7 (del7p) emerged as a recurrent defect. We mapped the common deleted region to the IKZF1 gene, which encodes the transcription factor Ikaros. We further examined the frequency of IKZF1 delet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
84
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(88 citation statements)
references
References 42 publications
2
84
0
2
Order By: Relevance
“…5 TET2, 6 ASXL1, 7 IDH1, IDH2, 8 CBL, 9 IKZF1, 10 LNK, 11 and EZH2. 12 Most of these mutations originate at the progenitor cell level but they do not necessarily represent the primary clonogenic event and are not mutually exclusive.…”
Section: Mplmentioning
confidence: 99%
“…5 TET2, 6 ASXL1, 7 IDH1, IDH2, 8 CBL, 9 IKZF1, 10 LNK, 11 and EZH2. 12 Most of these mutations originate at the progenitor cell level but they do not necessarily represent the primary clonogenic event and are not mutually exclusive.…”
Section: Mplmentioning
confidence: 99%
“…Steroids have been used to treat ITP for decades and are the most commonly used treatment for this disorder worldwide [9][10][11][12][13][14][15][16]. Although a majority of patients benefit from traditional steroid therapy, some are refractory to this treatment [11,12] as well as more recent steroid treatment protocols which utilize repeated pulses of high-dose DXM [13].…”
Section: Relative Efficacy Of Steroid Therapy In Immune Thrombocytopementioning
confidence: 99%
“…The fact that many of these mutations are infrequent and lack disease specificity further undermines their pathogenetic contribution to disease initiation [10]. On the other hand, the absence of mutual exclusivity and the higher prevalence of some MPN-associated mutations, such as IDH [14], LNK [15], IKZF1 [16], and TP53 [17] mutations, in blast-phase, as opposed to chronic-phase, MPN suggests possible pathogenetic contribution to leukemic transformation. Consistent with this contention, we recently showed that the presence of mutant IDH signified an increased risk of leukemic transformation in PMF [18] whereas others have demonstrated the same for EZH2 mutations [19].…”
mentioning
confidence: 99%
“…Examples are, respectively, mutations in MPL exon 10, found in around 5-10% of patients with ET or PMF [Pikman et al 2006;Guglielmelli et al 2007;Vannucchi et al 2008;Pardanani et al 2011c]; JAK2 exon 12 mutations in around 2-3% of V617F-negative patients with PV [Scott et al 2007;Passamonti et al 2011], CBL [Grand et al 2009] and LNK ; mutations in TET2, EZH2, ASXL1, members of the Polycomb Repressive Complex 2 (PCRC2), SF3B1 and SRSF2 [Carbuccia et al 2009;Delhommeau et al 2009;Ernst et al 2010;Guglielmelli et al 2011b]. However, mutations in IDH1/IDH2, Ikaros, p53, LNK and DNMT3A have been described preferentially at the time of AML evolution [Green and Beer, 2010;Jager et al 2010;Pardanani et al 2010;Abdel-Wahab et al 2011;Ha and Jeon, 2011;Harutyunyan et al 2011]. The molecular complexity of MPNs is incompletely understood and represents the focus of an intense research activity.…”
Section: Introductionmentioning
confidence: 99%